Comparative analysis of insertion torque and fracture resistance between two brands of infra-zygomatic crest screws - Ganga Bhavani Kolupuri; Satish Varma; Ujwala Paruchuri; Naga Sasidhar Yalavarthy (Mashhad University of Medical Sciences, 2023)
Objective: The present study aimed to determine the insertion torque and fracture resistance of infra-zygomatic crest (IZC) screws as critical factors influencing primary stability.Methods: A total of 40 stainless steel IZC mini-screw implants (MSIs) were obtained from two different manufacturers (Bio-Ray, Taiwan, and S. K. Surgicals, India). Each group comprised 20 MSIs of identical dimensions (2 ×14 mm). To simulate a clinical scenario, a customized jig was utilized to embed these screws into human maxillary bone blocks for evaluation of maximum insertion torque (MIT), and into polyacrylic glass blocks for assessment of fracture resistance. A digital torque gauge was used to obtain precise torque measurements.Results: There were significant differences in MIT between the groups at the tip and neck areas of the screws (P<0.05). The Bio-Ray IZC screws manifested significantly greater insertion torque at the tip and significantly lower insertion torque at the neck compared to the S.K. Surgicals group (P<0.05). However, the two groups demonstrated no significant difference in terms of fracture resistance (P=0.484).Conclusions: The evaluated mini-implants displayed a diverse range of insertion torques at various parts of the screws (increasing from tip to mid and neck regions). It is imperative to consider various torque values during screw insertion to mitigate the risk of tissue damage and screw breakage. The present findings revealed no significant difference in fracture resistance between the two brands of mini-implants, suggesting that the fracture torque was primarily influenced by factors beyond the manufacturer of the MSIs. (J Dent Mater Tech 2023;12(2): 91-97)